If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 12(3x + 4) + -6(2x + -3) = 4x + -74 Reorder the terms: 12(4 + 3x) + -6(2x + -3) = 4x + -74 (4 * 12 + 3x * 12) + -6(2x + -3) = 4x + -74 (48 + 36x) + -6(2x + -3) = 4x + -74 Reorder the terms: 48 + 36x + -6(-3 + 2x) = 4x + -74 48 + 36x + (-3 * -6 + 2x * -6) = 4x + -74 48 + 36x + (18 + -12x) = 4x + -74 Reorder the terms: 48 + 18 + 36x + -12x = 4x + -74 Combine like terms: 48 + 18 = 66 66 + 36x + -12x = 4x + -74 Combine like terms: 36x + -12x = 24x 66 + 24x = 4x + -74 Reorder the terms: 66 + 24x = -74 + 4x Solving 66 + 24x = -74 + 4x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-4x' to each side of the equation. 66 + 24x + -4x = -74 + 4x + -4x Combine like terms: 24x + -4x = 20x 66 + 20x = -74 + 4x + -4x Combine like terms: 4x + -4x = 0 66 + 20x = -74 + 0 66 + 20x = -74 Add '-66' to each side of the equation. 66 + -66 + 20x = -74 + -66 Combine like terms: 66 + -66 = 0 0 + 20x = -74 + -66 20x = -74 + -66 Combine like terms: -74 + -66 = -140 20x = -140 Divide each side by '20'. x = -7 Simplifying x = -7
| 6x=-x+147 | | z+17/23=-4/23 | | 7.26-0.3x=12 | | -2y-x-6=0 | | 5+2p-3=9p+4-6p | | g/9=-11 | | g/9=-1 | | 10e^6x=16 | | 5X-4=15+X | | 6(2x-1)-(11x+6)=7 | | 5/4x=20 | | x+54=70 | | -126= | | -6.1(4s+6)-1.8(2s-4)= | | 12-10=x/5 | | 18^7*6^2*3^-7/6^10 | | 9x-3x= | | r/6=-12 | | 3-18=3z | | 31/3/15/12= | | X^2-10=-9 | | 294.22/4.7 | | u^5+17u^4+80u^3= | | x/(-8)=6 | | f-7=-35 | | c/16=-1 | | -9(-4)+7=25+2(-4) | | y=0.6x+3 | | n/3+16=20 | | x^2-1/4x-3/64=0 | | 7w-49+6w+30=26 | | -7(x+3)+9=-12 |